Synthesis and Application of Deep Eutectic Solvents for the Deacidification of Waste Cooking Oil: A Pathway to High-Quality Biodiesel - Mutiara Putri; Leila Kalsum; Aida Syarif (Program Studi Pendidikan Biologi, 2026)
This study investigates the synthesis and application of deep eutectic solvents (DESs) for deacidifying waste cooking oil (WCO) to produce high-quality biodiesel. The research addresses conventional biodiesel production's economic and environmental challenges by using WCO as a cost-effective feedstock and employing DESs as a greener alternative to traditional solvents. DESs are biodegradable, have low toxicity, and can be easily prepared by mixing a hydrogen bond donor (HBD) and a hydrogen bond acceptor (HBA). The study synthesized DES using Choline Chloride (ChCl) as the HBA and ethylene glycol (EG) as the HBD at a constant temperature of 60° C and variable stirring rates of 150 and 200 rpm. Five different molar ratios of ChCl to EG were tested: 1:1, 1:2, 1:4, 1:6, and 1:8. The effectiveness of the DESs was evaluated based on their ability to remove free fatty acids (FFAs) from WCO, with DES 2 (1:2 molar ratio) and DES 3 (1:4 molar ratio) showing the highest adsorption efficiencies. The research also characterized the resulting biodiesel, comparing key properties such as cetane number, sulfur content, and flash point to established standards. The results show that increasing the DES concentration significantly enhances the removal of FFAs, with DES 2 achieving an 84% efficiency and DES 3 achieving an 83% efficiency at a 1:6 WCO: DES molar ratio. DES treatment consistently improved key fuel properties: the cetane number increased, while sulfur content and total acid number (TAN) were significantly reduced. DES 3 emerged as the most effective solvent, yielding the highest cetane number (56.3), lowest sulfur content (18 ppm), and lowest TAN (0.12 mgKOH/g) at the 1:6 molar ratio. While DES treatment reduced the fuel's flash point, the overall benefits of producing a cleaner, higher-quality fuel outweigh this concern. This research confirms that DESs provide a sustainable and practical pathway for producing high-quality biodiesel from waste cooking oil